EXTERNAL PUBLIC DEBT AND ECONOMIC GROWTH IN KENYA - MUINGA, RUTH MUENDI (My University, 2014)
This study examines the relationship between external public indebtedness and economic growth in Kenya. It uses data from 1970 to 2010from World Development Indicators and Kenya National Bureau of Statistics. The GDP is theproxy for economic growth.The explanatory variables are capital, labour, interest payments on external debt, external public debt, debt service payments,and inflation. Since the data isin time series the augmented Dickey Fuller Unit Root testis used to ascertain stationarity.The econometric technique of Ordinary Least Square (OLS) is employed in the data analysis.The results indicate that external debt and interest payments on external debt payments contribute negatively to economic growth in Kenya. Capital formation and labour force have a significant positive contribution to economic growth.The simulation results show that any percentage increase of external debt holding other factors constant, will reduce the GDP hence slow economic growth.The study recommends that the policies of debt management in Kenya be reviewed and improved. The government should pay more attention to the debt management profile particularly on the expenditure items and diversify the economy to generate more revenue and avoid external borrowing to the extent possible